ANALYSIS OF PHOSPHORUS AND POTASSIUM LEVELS IN ORGANIC FERTILIZER IN THE INTEGRATED LABORATORY OF JOMBANG DISTRICT AGRICULTURE OFFICE - Zakiyah, Zahrah Nur; Rahmawati, Cicik; Fatimah, Is (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2018)
Quantitative analysis in the integrated laboratory of Jombang District Agriculture Office has been done on two samples of organic fertilizer with phosphorus and potassium parameters, considering these two elements are macronutrients which have an important role in the growth and development of plants. Determination of phosphorus level has been done by ascorbic acid method using double beam UV-Visible spectrophotometer, while determination of potassium level has been done by flame photometric method. There are 2 samples code of organic fertilizer, 13/F/16 and 14/F/16. From the result of analysis, the phosphorus level as P2O5 in 13/F/16 sample is 0.275%, while in the 14/F/16 sample is 0.29%. The potassium level as K2O in 13/F/16 sample is 2.58%, while in the 14/F/16 sample is 2.67%. These results meet the requirements for compost quality standards based on SNI 19-7030-2004, because they exceed the minimum requirements, which are 0.10% for phosphorus level and 0.20% for potassium level.